Legal Reform in Uzbekistan: Prospects for Freedom of Religion or Belief and Covenantal Pluralism - Clark, Elizabeth A. (The review of faith & international affairs, 2020)
This article examines religious legislation reform in Uzbekistan since 2017, when President Shavkat Mirziyoyev took power after the death of his predecessor Islam Karimov. The article evaluates to what extent the reforms that the Uzbek government has been trying to implement in recent years are advancing religious freedom in Uzbekistan, and to what extent they are helpful in developing covenantal pluralism. The article argues that Uzbekistan has made some progress in furthering freedom of religion or belief for all, thereby improving prospects for covenantal pluralism. However, there are still serious obstacles preventing believers, and especially religious minorities, from full enjoyment of freedom of religion and liberty of conscience.